ANALISIS YURIDIS TERHADAP PELAKSANAAN GUGATAN PERBUATAN MELAWAN HUKUM TERHADAP WARGA NEGARA ASING DI BALI - Stephanie Priscilla Darmawan (LPPM Institut Pendidikan Nusantara Global, 2023)
Bali as an international tourist destination has many foreign nationals who live and carry out activities there. However, sometimes legal disputes occur between foreign nationals and other parties in Bali, resulting in unlawful acts lawsuits being filed against foreigners. Therefore, a juridical analysis is needed on the implementation of lawsuits against foreigners in Bali. This study aims to analyze legally the implementation of lawsuits against foreigners in Bali and provide a clearer understanding of procedures and legal guidelines for litigation of lawsuits against foreign nationals in Bali. Normative juridical research with literature study is the method used in this research. By using content analysis technique, the data obtained will be examined qualitatively. The results of the study show that the procedure for lawsuits against foreigners in Bali is the same as for lawsuits against Indonesian citizens. According to Indonesian laws and regulations, foreigners who violate the law in Bali may be subject to criminal charges and/or administrative sanctions. Courts in Bali will try cases of unlawful acts of foreign nationals by considering national law, international law, and the principle of justice. In addition, there are risks in suing foreign nationals, such as difficulties in gathering evidence and limitations on execution laws abroad.